Characterization of a Panel of Monoclonal Antibodies Targeting the F-Protein of the Respiratory Syncytial Virus (RSV) for the Typing of Contemporary Circulating Strains - Vera Krivitskaya; Ekaterina Petrova; Evgeniy Sorokin; Tatyana Tsareva; Maria Sverlova; Kseniia Komissarova; Anna Sominina; Daria Danilenko (Tropical Medicine and Infectious Disease, 2023)
Respiratory syncytial virus (RSV) is the most common cause of upper and lower respiratory tract infections in infants and young children. Virus-specific monoclonal antibodies (mAbs) can be used for diagnosis, prophylaxis, and research of RSV pathogenesis. A panel of 16 anti-RSV mAbs was obtained from mice immunized by RSV strain Long. Half of them had virus-neutralizing activity. According to Western blot all of these mAbs effectively bound native oligomeric (homodimeric and homotrimeric) forms of the RSV fusion (F) protein. Only five of the mAbs interacted with the monomeric form, and only one of these possessed neutralizing activity. None of these mAbs, nor the commercial humanized neutralizing mAb palivizumab, reacted with the denaturated F protein. Thus, interaction of all these mAbs with F protein had clear conformational dependence. Competitive ELISA and neutralization assays allowed the identification of nine antigenic target sites for the interaction of mAb with the F protein. Five partially overlapping sites may represent a complex spatial structure of one antigenic determinant, including one neutralizing and four non-neutralizing epitopes. Four sites (three neutralizing and one non-neutralizing) were found to be distinct. As a result of virus cultivation RSV–A, strain Long, in the presence of a large amount of one of the neutralizing mAbs, an escape mutant with a substitution, N240S, in the F protein, was obtained. Thus, it was shown for the first time that position 240 is critical for the protective effect of an anti-RSV antibody. To assess the ability of these mAbs to interact with modern RSV strains circulating in St. Petersburg (Russia) between 2014 and 2022, 73 RSV-A and 22 RSV-B isolates were analyzed. Six mAbs were directed to conserved epitopes of the F protein as they interacted most efficiently with both RSV subtypes in a fixed cell-ELISA and could be used for diagnostic assays detecting RSV.